2017
DOI: 10.3390/app7121220
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Road Simulator for Motorcycle Applications

Abstract: Four-wheeled vehicles are often tested on indoor, four-poster road simulator rigs. Road loads are simulated with the use of servo-hydraulic systems for suspension set-up optimisation, NVH analysis, and fatigue life cycles. The use of a road simulator is not such a common practice for two-wheeled vehicles despite problems to be faced being extremely similar. The paper presents a device for testing motorcycles on a Servotest ® four-poster. A dedicated restraint system had to be devised in order to support the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…(11) These and other studies indicate that FEM is a reliable numerical calculation method and that the FEM analyses of electric motorcycle frames can effectively be used to correct design flaws. (12)(13)(14) For example, Rodriguez et al utilized SolidWorks drawing software to create a 3D model of a two-wheeled motorcycle, which was then imported into FEM software to generate an analysis model. (15) They also analyzed the drive system and telescopic mechanism models, and the results were utilized as a reference for dynamic design.…”
Section: Introductionmentioning
confidence: 99%
“…(11) These and other studies indicate that FEM is a reliable numerical calculation method and that the FEM analyses of electric motorcycle frames can effectively be used to correct design flaws. (12)(13)(14) For example, Rodriguez et al utilized SolidWorks drawing software to create a 3D model of a two-wheeled motorcycle, which was then imported into FEM software to generate an analysis model. (15) They also analyzed the drive system and telescopic mechanism models, and the results were utilized as a reference for dynamic design.…”
Section: Introductionmentioning
confidence: 99%
“…In the work [1,3,16] the issue of building simulation stations that cause vibrations of individual elements and motorcycles was addressed. Research mainly involved the development of a model of vibrations occurring in the vehicle, the limitation of steering-wheel vibrations, and the study of the vehicle's strength.…”
Section: Introductionmentioning
confidence: 99%
“…This is also highlighted in Gadola and Chindamo, 13 a recent paper describing the authors' own experience through a case study, and stating that among the various benefits, the intensive design, manufacturing, and testing activities related to these competitions have promoted applied research, as shown by the following publications. Vibration testing on a four-poster rig and the development of an experimental suspension friction model, to be incorporated into FSAE vehicle dynamics simulations, are described in Benini et al 14 Experimental, fourposter-based testing on vehicles is also dealt with in Chindamo et al [15][16][17] A fuzzy logic-based approach to energy management on a hybrid high-performance vehicle is described in Chindamo et al 18 The application of neural networks to a typical problem related to vehicle state estimation in vehicle dynamics is dealt with in Gadola and Chindamo. 19 Other papers are related to human-vehicle interaction like Crema et al, 20 focused on physiological body response when driving a FSAE car in a competitive environment, and Gritti et al, 21 describing how friction affects driver's feedback from the steering system, as well as the results of a related experimental campaign.…”
Section: Introductionmentioning
confidence: 99%
“…14 Experimental, four-poster-based testing on vehicles is also dealt with in Chindamo et al. 1517 A fuzzy logic-based approach to energy management on a hybrid high-performance vehicle is described in Chindamo et al. 18 The application of neural networks to a typical problem related to vehicle state estimation in vehicle dynamics is dealt with in Gadola and Chindamo.…”
Section: Introductionmentioning
confidence: 99%